Implementation of Islamic Sharia Law in Social Life - Ii Sumantri (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
Implementing Islamic shari'ah in people's lives is not an easy thing. However, a serious effort is needed because, in the implementation process, there will be obstacles, both from internal Muslims themselves and external Muslims. The author of this paper uses the literature review method, which is a series of activities related to the method of collecting library data, reading, recording, and processing materials that are appropriate for the theme of the discussion and can be taken from library sources, either in the form of books, articles, journals, manuscripts. Publications and so on, where these sources contain theories relevant to the discussion. In this article, it can be concluded that the importance of obtaining correct information about Islamic Sharia law and how it can lead to positive attitudes and actions. In addition, this article also discusses the challenges in implementing Islamic Sharia law in social life